Lateral ventral spontaneous hernia.: Five new cases. - Croci, Fabio; Belloso, Rogelio (Cirugía del Uruguay, 1984)
The spontaneous lateral ventral hernia is extended and variad, predominantly in old age and frequently, has occlusive complications (43% of the cases). In this work, the nineteen cases known locally are compilad together with five new cases. The whole-series is discussed, considering etiopathogenic, clinical, anatomopathological and therapeutic aspects of this variety of hernia.